Therapy of Chagas Disease: Implications for Levels of Prevention - Sergio Sosa-Estani; Lisandro Colantonio; Elsa Leonor Segura (Journal of Tropical Medicine)
This paper reviews the evidence supporting the use of etiological treatment for Chagas disease that has changed the standard of care for patients with Trypanosoma cruzi infection in the last decades. Implications of this evidence on different levels of prevention as well as gaps in current knowledge are also discussed. In this regard, etiological treatment has shown to be beneficial as an intervention for secondary prevention to successfully cure the infection or to delay, reduce, or prevent the progression to disease, and as primary disease prevention by breaking the chain of transmission. Timely diagnosis during initial stages would allow for the prescription of appropriate therapies mainly in the primary health care system thus improving chances for a better quality of life. Based on current evidence, etiological treatment has to be considered as an essential public health strategy useful to reduce disease burden and to eliminate Chagas disease altogether.